Listeria monocytogenes serotype 4b strains replicate in monocytes/macrophages more than the other serotypes - HASEBE, Rie (J Vet Med Sci, 2017)
We analyzed the pathogenicity of various serotypes of Listeria monocytogenes using a Balb/c mouse intravenous injection model. The survival rates of mice inoculated with strains NS1/2b (serotype 1/2b), NS3b (serotype 3b) and NS 4b (serotype 4b) were 60, 63.6 and 63.6%, respectively. Although the survival rates were similar, the bacterial growth in the liver of NS3b-infected mice was 144.5-fold higher than that in the liver of NS4b-infected mice. Histopathological analyses suggest that the NS4b strain replicated more in monocytes/macrophages, whereas the NS3b strain replicated more in hepatocytes. These results raise a possibility that the serotype 4b strains replicated more in monocytes/macrophages compared to the other serotype strains. To assess this, we isolated CD11b-positive cells from mouse livers infected with EGDe (serotype 1/2a), NS1/2b, NS3b, NS4b and the serotype 4b strains 51414 and F17 and counted the number of live bacteria in these cells. CD11b-positive cells from the NS4b-, 51414- and F17-infected mice possessed 24.4- to 42.7-fold higher numbers of live bacteria than those from mice infected with EGDe and NS3b strains. These results suggest that serotype 4b strains replicated more in monocytes/macrophages than the other serotypes, and this may be involved in the pathogenicity of serotype 4b strains, particularly in the dissemination of L. monocytogenes through the host body.